Pengaruh Pembelajaran Mikrobiologi terhadap Pengetahuan Mahasiswa Kesehatan tentang Pencegahan Penyakit Menular Seksual - Siti Julaikha; Kardi (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
Health students' knowledge of the prevention of Sexually Transmitted Diseases (STDs) is essential to support their role as health workers in the future. This study aims to analyze the influence of learning Microbiology courses on increasing health students' knowledge about STD prevention. The research method uses a quasi-experimental design with a pre-test and post-test approach. The research sample was 60 students in the two semester of the DIII Pharmacy study program, Bima International University, MFH, selected by purposive sampling technique. The instrument used was a knowledge questionnaire about STDs. The data was analyzed by the paired sample t-test. The results showed a significant increase in student knowledge after participating in Microbiology learning (p < 0.05). The conclusion of this study is that learning Microbiology has a positive effect on increasing health students' knowledge about STD prevention.